2014
DOI: 10.1002/jcp.24640
|View full text |Cite
|
Sign up to set email alerts
|

Combined EGFR and Autophagy Modulation Impairs Cell Migration and Enhances Radiosensitivity in Human Glioblastoma Cells

Abstract: Glioblastoma (GBM) remains the most aggressive and lethal brain tumor due to its molecular heterogeneity and high motility and invasion capabilities of its cells, resulting in high resistance to current standard treatments (surgery, followed by ionizing radiation combined with Temozolomide chemotherapy administration). Locus amplification, gene overexpression, and genetic mutations of epidermal growth factor receptor (EGFR) are hallmarks of GBM that can ectopically activate downstream signaling oncogenic casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Autophagy is a double-edged sword in tumour progression and treatment: it can either facilitate cancer survival under metabolic stress or induce autophagic tumour cell death [35,36]. Mounting evidence accumulated in recent years suggests that inhibition of autophagy can reduce the treatment resistance of chemotherapy and radiotherapy in various types of cancers [37,38], which is also the case in GBM treatment [39,40]. To clarify the role of autophagy in peiminine therapy for GBM, LN229 and U251 cells were observed under TEM after peiminine treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a double-edged sword in tumour progression and treatment: it can either facilitate cancer survival under metabolic stress or induce autophagic tumour cell death [35,36]. Mounting evidence accumulated in recent years suggests that inhibition of autophagy can reduce the treatment resistance of chemotherapy and radiotherapy in various types of cancers [37,38], which is also the case in GBM treatment [39,40]. To clarify the role of autophagy in peiminine therapy for GBM, LN229 and U251 cells were observed under TEM after peiminine treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, autophagy can positively or negatively regulate both GBM invasion and resistance to therapy, the two hallmarks of GBM aggressiveness. 85 Concerning invasion and cell motility, whereas Catalano et al 86 reported an impairment of migration and invasion of GBM cells after autophagy induction, Palumbo et al 87 noticed this impairment after autophagy inhibition, especially when EGFR was coinhibited, thus highlighting the importance of growth factor signaling.…”
Section: Autophagy and Gbmmentioning
confidence: 99%
“…A study by Lomonaco et al 33 provided evidence that inhibition of autophagy enhanced CD133+ glioblastoma stem cell sensitivity to ionizing radiation after bafilomycin treatment or Atg5 silencing. Notably, Palumbo et al 30 found that Atg7 silencing resulted in reduced T98 cell sensitivity to radiation and to a combination of radiation with anti-EGFR therapy 34 , indicating a complex role of different Atgs in radiation response. …”
Section: Discussionmentioning
confidence: 99%